COMPARISON OF ANTIHYPERGLYCEMIC ACTIVITY OF DIFFERENT PARTS OF KLUTUK BANANA (MUSA BALBISIANA COLLA) - NOFIANTI, TITA; MUHTADI, AHMAD; FIDRIANNY, IRDA (International Journal of Applied Pharmaceutics, 2021)
Objective: Banana is a plant that grows in Indonesia and is widely consumed by Indonesian people. One of banana type is klutuk banana (Musa balbisiana Colla). There were many types of researches about klutuk banana for antidiabetic activity; however, antidiabetic activity of its peel and pulp are still unknown. Methods: The objective of the study was to determine of antihyperglycemic activity of different parts of klutuk banana. Animals were divided into 15 groups, namely normal control, negative control, positive control (glibenclamide 0.65 mg/kg body weight (bw), and 12 sample groups. All animals were given 2 g/kg bw glucose monohydrate and blood glucose level was measured every 30 min for 120 min. Results: The results of the oral glucose tolerance test (OGTT) showed that KPE2 (klutuk peel extract 350 mg/kg bw) gave higher activity to decrease blood glucose level compared to the other groups at the minute of 30 (-24.83%; p. 0.00), 60 (-33.93%; p. 0.000), 90 (-46.29%; p. 0.000) and 120 (-35.44%; p. 0.000). Conclusion: The klutuk peel extract has very strong antioxidant activity and antihyperglycemic activity at a dose of 350 mg/kg bw.